STRATEGI 4R DALAM PENGELOLAAN SAMPAH: MENDUKUNG EKONOMI DAN LINGKUNGAN LESTARI DI KOTA LHOKSEUMAWE - muhammad lutfi Al Fahmi; Shalawati Shalawati; Mulia Andirfa; Bobby Rahman; Ardian Baharuddin; Azra Lailatul Fitri (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Unplanned waste management practices will give rise to more complex and detrimental social problems. Indiscriminate dumping of rubbish, burning rubbish and piling rubbish in public places are habits that cause air and land pollution, which ultimately has an impact on high ground water levels and causes obstruction of water channels which ultimately results in flooding. Waste management issues must be investigated and addressed by all stakeholders as soon as possible. Waste cannot be handled carelessly; rather, it requires a comprehensive approach that involves all stakeholders to solve it, turning it from a societal problem into one that adds value to managers' profits and protects the environment. Uncertainty regarding the importance of 4R-based waste management is still a major problem in society. This situation then encourages the development of new problems related to waste, such as unpleasant views, strong odors, and disturbed environmental conditions. Environmental and social problems are also caused by the increasing amount of waste thrown into landfills in the surrounding environment. The aim of this service project is to increase public awareness of the possible risks associated with waste and the importance of keeping the environment clean. As a genuine effort to control waste and offer alternative options to strengthen the community's economy, this activity will provide an overview to the community regarding the economic possibilities and opportunities of 4R-based waste management. By implementing a 4R-based waste management program, the people of Lhokseumawe City can maximize waste as a source of income. By sorting waste and selling it to collectors, people can earn additional income from waste. Apart from that, this waste management program can also open up new business opportunities for the community, such as processing organic waste into fertilizer or eco enzymes. This service activity will be carried out for one year in 2023 by producing mandatory outputs in the form of increasing the community's knowledge and skills in managing their waste using 4R, publication in the ISSN Service Journal, publication on electronic media and activity videos.